2013
DOI: 10.1371/journal.pone.0076934
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Prostanoid Pathway in the Ovary Development of the Penaeid Shrimp Penaeus monodon

Abstract: The prostanoid pathway converts polyunsaturated fatty acids (PUFAs) into bioactive lipid mediators, including prostaglandins, thromboxanes and prostacyclins, all of which play vital roles in the immune and reproductive systems in most animal phyla. In crustaceans, PUFAs and prostaglandins have been detected and often associated with female reproductive maturation. However, the presence of prostanoid biosynthesis genes remained in question in these species. In this study, we outlined the prostanoid pathway in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 56 publications
1
56
0
Order By: Relevance
“…Significant up-regulation of PmCOX, PmPGFS, and PmPGES1 gene expression was observed in the HIGH group, whilst PmPGES3 was significantly up-regulated in the LOW group. The up-regulation of PmPGFS in the HIGH group is noteworthy, given its role in regulating the onset of maturation and the previously demonstrated reduction in PmPGFS gene expression in ovaries mature (Wimuttisuk et al, 2013). Within P. monodon ovaries, oocytes migrate radially away from the site of proliferation and therefore it is possible for oogonia, primary oocytes and mature oocytes to be present simultaneously within mature ovaries (Tanfermin and Pudadera, 1989).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Significant up-regulation of PmCOX, PmPGFS, and PmPGES1 gene expression was observed in the HIGH group, whilst PmPGES3 was significantly up-regulated in the LOW group. The up-regulation of PmPGFS in the HIGH group is noteworthy, given its role in regulating the onset of maturation and the previously demonstrated reduction in PmPGFS gene expression in ovaries mature (Wimuttisuk et al, 2013). Within P. monodon ovaries, oocytes migrate radially away from the site of proliferation and therefore it is possible for oogonia, primary oocytes and mature oocytes to be present simultaneously within mature ovaries (Tanfermin and Pudadera, 1989).…”
Section: Discussionmentioning
confidence: 86%
“…Prostanoids derived from ARA (i.e. series II prostaglandin) have significant roles in the onset of maturation, stimulation and sequestration of egg yolk and development of essential cellular machinery such as cortical rods in P. monodon (Wouters et al, 2001a, Meunpol et al, 2010, Wimuttisuk et al, 2013. It has previously been reported that the ARA:EPA ratio in mature ovaries of wild P. monodon range from 0.3-0.6 (Crocos, 1997, Marsden et al, 1991, D'Souza and Kelly, 2000, Wouters et al, 2001a, Huang et al, 2008, whilst the diet used by Coman et al (2011) contained a ARA:EPA ratio of 0.5 and resulted in a ratio of 0.57 in spawned eggs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations